Characterization of a Novel Polyalthia Longifolia Mid-rib Fibers as a Potential Reinforcement for Polymer Composites. Issue 6 (3rd June 2022) - Shenoy Heckadka, Srinivas; Nayak, Suhas Yeshwant; Kamath, C. Raghavendra; Adarsh, S. P.; Samant, Rashmi
Abstract: This research work makes use of a novel polyalthia longifolia leaf mid-rib fibers as a potential reinforcement for polymer composites. The fibers were subjected to sodium hydroxide treatments for different duration, and its effect on the tensile strength of the polyalthia fibers was examined. 6 h treatment was found to be optimum with a maximum tensile strength of 134 MPa. Scanning electron microscopy of the fiber surface revealed surface impurities, waxy granules and breakage of fibrils as some of the prominent features for variation in tensile strength. Fourier transform infrared spectra of all varieties of fibers supported function group modifications. Polyester-based composites were fabricated with 6 h treated fibers, and their mechanical properties were determined. Maximum values of tensile, flexural and impact strength obtained were 43MPa, 35MPa and 12 kJ/m 2 respectively. Fiber breakage, fiber pull-out and de-bonding were some of the fracture mechanisms observed through scanning electron micrographs of the polyalthia longifolia composites.